Profil Peternak Kambing Peranakan Etawa Di Desa Gumelar Kabupaten Banyumas - Febri Edi Saputra; Sari Tuswati; Doso Sarwanto; Soegeng Herijanto (Fakultas Peternakan. Unwiku, Purwokerto, 2025)
The study entitled Profile of Etawa Crossbred Goat Breeders (PE) in Gumelar Village, Gumelar District, Banyumas Regency was conducted on August 16 - September 17, 2024 in Gumelar Village. The formulation of the problem in this study is 1) How old are the breeders in Gumelar Village. 2) How is the education of the breeders in Gumelar Village. 3) How many dependents are there in the breeder's family in Gumelar Village. 4) How long have they been raising livestock. This study used a survey method by collecting information from goat breeders in Gumelar Village. The variables observed included the age of the breeder, the breeder's education, the number of dependents in the family, and the experience of raising livestock in Gumelar Village. The results of the study showed, 1). Most of the PE goat breeders in Gumelar Village were over 55 years old, 2). Most of the PE goat breeders' education graduated from elementary school, 3). Most of the PE goat breeders have 3-5 family dependents, 4). Most of the breeders have 11-30 years of livestock experience.